Characterization of Immune Response Against Mycobacterium marinum Infection in Coho Salmon (Oncorhynchus kisutch) - Le Li; Danlei Xu; Xiaoqing Yu; Chunlei Gai; Haibin Ye; Jing Diao (Fishes, 2025)
Mycobacterium marinum is an opportunistic pathogen prevalent in aquatic environments, causing significant morbidity in fish, including Coho salmon (Oncorhynchus kisutch), a species increasingly cultured in Chinese salmonid aquaculture. This study investigated the immune response of Coho salmon to M. marinum infection and the bacterial proliferation dynamics in the liver and kidney. Transcriptome analysis revealed 5028 differentially expressed genes (DEGs) in the kidney and 3419 DEGs in the liver at 6 weeks post-infection. Gene Ontology and KEGG enrichment analysis highlighted pathways such as cytokine–cytokine receptor interaction, metabolic pathways, and Toll-like receptor signaling in the kidney, while the DEGs in the liver were enriched in metabolic pathways, immune system processes, and stress and defense responses. The temporal expression profiling of 15 immune-related genes, including acute-phase proteins (serum amyloid A-5 and hepcidin), cytokines (TNF-α, IL-1β, IL-17A), chemokines (CXCL13 and CCL19), pattern recognition receptors (Toll-like receptor 13), and other immune-related genes, showed significant upregulation against M. marinum infection, with stronger responses in the liver. Furthermore, it was found that there was a progressive proliferation of M. marinum in the infected liver and kidney from approximately 2.5 log10 cfu/g at week 2 to about 6 log10 cfu/g by 6 weeks, with a significantly higher load in the liver. These findings provide critical insights into the immune mechanisms of Coho salmon against M. marinum and the pathogen’s tissue-specific proliferation, offering a foundation for developing targeted control strategies against M. marinum in aquaculture.